Quality Control of a Marine Origin Based Herbo-Mineral Unani Formulation (Indo-American Journal of Life Sciences and Biotechnology, 2022)
Unani doctors have long relied on a coral mixture called Kushta Marjan (KM) to cure a wide range ofillnesses. In its internal form, kushta, coral—the calcareous skeleton of the little marine creature thatbelongs to the phylum coelenterate—is used. Cough, asthma, and anorexia are conditions in which it workswell. There has been no research to far that can be used to develop KM quality control. Thermogravimetricanalysis (TGA), differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FTIR),and classical testing have all contributed to illuminating KM's preparation methods, structural, functional,and physico-chemical properties in this study. A number of compounds were identified in the FTIR spectra,including organic compounds, calcium oxide, and others. The DSC curve showed maxima at 20°C, 65°C,183°C, and 261°C, and the total weight loss throughout TGA was 30.09%. The findings might serve as abenchmark for kushta marjan and inform future efforts to standardize and refine KM in regular analysis,given that this is the first research of its kind.